Stable route selection and network load reduction in wireless ad hoc networks / Kok Gin Xian - Kok, Gin Xian (2015)
A wireless ad hoc network is a dynamic communication network formed by decentralized wireless devices called nodes located, arranged, and moving arbitrarily without the support of a pre-installed infrastructure. The properties of wireless ad hoc networks such as node mobility, multi-hop communication, and self-configuration make them rapidly deployable and flexible. However, the same properties that provide these benefits also result in some issues. For example, node mobility results in frequent network topology changes. Routes that are built over a highly dynamic network are vulnerable to breakage, which leads to interruptions in data transmission and packet loss. To reduce the detrimental effects of node mobility on the network performance, two routing metrics to guide nodes in discovering and establishing stable routes are proposed. The central idea is to select routes consisting of shorter links and/or links formed by low mobility nodes over other routes. A drawback of using link length and node mobility information is that hardware sensors such as global positioning system (GPS) sensors are required. We overcome this inconvenience by proposing a method to estimate the link length between two nodes, and also a method to estimate the relative node mobility of a node with respect to its neighboring nodes. Through our investigation, we found that the proposed routing metrics to be effective in guiding nodes discover and establish routes that are more stable. As a result of using routes that are more stable, higher network performance is achieved. The same property that allows a wireless ad hoc network to span a large area, i.e., multi-hop communication also results in worse network throughput. This is because multi-hop communication results in higher network load as the delivery of a packet from the source to the destination may require several packet transmissions. Network coding is an efficient method that can reduce the network load. We propose an ad hoc routing protocol called Network Coding Routing (NCRT). In NCRT, a new set of coding conditions to find more coding opportunities was established, and a coding-aware and load-aware routing metric is available to guide source nodes in selecting better paths for sending their packets. Due to reduced network load and improved path selection, NCRT outperforms existing network coding and non-network coding routing protocols. In addition to increasing the network load, the multi-hop structure in wireless ad hoc networks and the decentralized nature of the nodes make broadcasting a complex and inefficient operation. On the one hand, the transmission from a source node may not reach every other node in the network; hence, other nodes need to decide whether to forward the packet when they receive it. On the other hand, if every node forwards the packet that it receives, many redundant transmissions may be resulted in the network. To resolve this problem, we propose an enhanced broadcast protocol for wireless ad hoc networks that reduces the number of redundant transmissions while maintaining packet reachability to all nodes in a network.